Narrative Organization Deficit in Lewy Body Disorders Is Related to Alzheimer Pathology - Grossman, Murray; Irwin, David J.; Jester, Charles; Halpin, Amy; Ash, Sharon; Rascovsky, Katya; Weintraub, Daniel; McMillan, Corey T. (Frontiers in Neuroscience, 2017)
BACKGROUND: Day-to-day interactions depend on conversational narrative, and we examine here the neurobiological basis for difficulty organizing narrative discourse in patients with Lewy body disorders (LBD). METHOD: Narrative organization was examined in 56 non-aphasic LBD patients, including a non-demented cohort (n=30) with Parkinson’s disease (PD) or PD-Mild Cognitive Impairment PD-MCI), and a cohort with mild dementia (n=26) including PD-dementia (PDD) and dementia with Lewy bodies (DLB), with similar age and education but differing in MMSE (p<0.001). We used a previously reported procedure that probes patients’ judgments of the organization of brief, familiar narratives (e.g. going fishing, wrapping a present). A subgroup of 24 patients had MRI assessment of regional gray matter (GM) atrophy and cerebrospinal fluid (CSF) levels of biomarkers for Alzheimer’s disease (AD) pathology, including beta amyloid (Aβ), total-tau (t-tau), and phosphorylated-tau (p-tau). RESULTS: Mildly demented LBD patients had a significant deficit judging narratives compared to non-demented patients, but this deficit was not correlated with MMSE. Regression analyses instead related narrative organization to regions of frontal GM atrophy, and CSF levels of Aβ and t-tau associated with presumed AD pathology in these frontal regions. CONCLUSION: These findings are consistent with the hypothesis that CSF markers of AD pathology associated with frontal regions play a role in difficulty organizing narratives in LBD.